Production of germ-line chimeras in zebrafish by cell transplants from genetically pigmented to albino embryos. - Lin, S (1992)
To determine whether embryonic cells transplanted from one zebrafish embryo to another can contribute to the germ line of the recipient, and to determine whether pigmentation can be used as a dominant visible marker to monitor cell transplants, we introduced cells from genetically pigmented (donor) embryos to albino recipients at midblastula stage. By 48 hr many of the resulting chimeras expressed dark pigment in their eyes and bodies, characteristics of donor but not albino embryos. By 4-6 weeks of age pigmentation was observed on the body of 23 of 70 chimeras. In contrast to fully pigmented wild-type fish, pigmentation in chimeras appeared within transverse bands running from dorsal to ventral. Pigmentation patterns differed from one fish to another and in almost every case were different on each side of a single fish. At 2-3 months of age chimeras were mated to albino fish to determine whether pigmented donor cells had contributed to the germ line. Of 28 chimeric fish that have yielded at least 50 offspring each, 5 have given rise to pigmented progeny at frequencies of 1-40%. The donor cells for some chimeras were derived from embryos that, in addition to being pigmented, were transgenic for a lacZ plasmid. Pigmented offspring of some germ-line chimeras inherited the transgene, confirming that they descended from transplanted donor cells. Our ability to make germ-line chimeras suggests that it is possible to introduce genetically engineered cells into zebrafish embryos and to identify the offspring of these cells by pigmentation at 2 days of age.